Financing elderly care in Italy and Europe. Is there a common vision? - Elenka Brenna; Lara Gitto (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2016)
There is a general consensus in considering the public financing for LTC as a suitable proxy of the resources committed to elderly care by each Government. But the preciseness of this approximation depends on the extent to which LTC is representative of elderly care within a country. We investigate this issue by estimating the resources specifically spent on elderly assistance in Lombardy, an Italian region which in terms of population, dimension, health care organization and economic development could be compared to many European countries, such as Sweden, Austria or Belgium. The analysis focuses on the public financing on elderly care in Italy and, in particular, in Lombardy, both in terms of organizational level (central/regional/local) and governmental responsibility (Welfare/Social Department). Quantitative data on the financing of elderly care is drawn from the national and regional balances; the provision of services is analyzed using regional and community based data. Results address two main questions. First, they highlight the absence of an appropriate method for assessing the public resources committed by each European country to LTC elderly expenditure. Second, our findings suggest an overestimate of the funding actually spent for elderly care in Italy: this should be of warning for policy makers, especially in view of an increasing ageing of the population.
Keywords: H53; H72; I38; 330; LTC financing; elderly care; European LTC policies